Transformasi Digital pada Pembelajaran Pengembangan Sosial Emosional di Taman Kanak-Kanak - Ristiyati Ristiyati; Dian Hidayati (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
Rapid digital transformation is changing perspectives on learning. Traditional methods are being eroded in favor of digitally responsive knowledge. In education, both teachers and students should be able to leverage digital transformation. Therefore, this research aims to analyze the extent of digital technology utilization in the social-emotional development aspect of kindergarten education. The researcher conducted surveys, interviews, observations, and documentation to gather data. The research findings indicate that the utilization of digital media is highly effective in detecting and exploring the deep-seated social-emotional development, including student engagement, creativity, interests, respect for others, and overall well-being. These goals can be achieved well and to their fullest extent.